Financing Entrepreneurship in Post-Covid-19 Era: The Islamic Banking and Finance Option - AbdulFattah AbdulGaniyy; Ibraheem Alani AbdulKareem; Aminu AbdulRaheem (Universitas Muhammadiyah Yogyakarta, 2021)
Entrepreneurship is the bedrock that propels the development and growth of the economy. Unfortunately, access to finance is the major obstacle faced by entrepreneurs. Conventional banking does not support innovative and dynamic ideas driven by entrepreneurs. They are required to pay back loans with interest collected from conventional banks without regard to the success or failure of their venture. Islamic bank has come to the rescue of entrepreneurs through its inventive Profit and Loss Sharing (PLS) products and services. The objective of this study was to highlight features and products of Islamic banking and finance that are suitable for entrepreneurship. The study was a conceptual and adopted method of reviewing existing literature on financing entrepreneurship and its challenges. The authors concluded that Islamic finance provides a better alternative to conventional finance and provides stability and sustainability to entrepreneurs. The study recommended that government should support and encourage entrepreneurs to cooperate with Islamic banks. There should be continuous public education, especially of the youth on skill acquisition through entrepreneurship centers. The study has implications for the government, policymakers and other stakeholders responsible for providing palliatives to the citizens in the post-covid-19 pandemic. Islamic finance is more aligned and supportive of entrepreneurship, especially through its profit and loss sharing financing.